2-Hydroxy-N′-(2-hydroxy-3-methoxy-5-nitrobenzylidene)-3-methylbenzohydrazide - Han, You-Yue (International Union of Crystallography, 2010)
In the title compound, C(16)H(15)N(3)O(6), the dihedral angle between the two benzene rings is 0.9 (2)°. The molecule adopts an E configuration with respect to the C=N bond. There are intramolecular O—H⋯N and O—H⋯O hydrogen bonds in the molecule. In the crystal structure, molecules are linked through intermolecular N—H⋯O hydrogen bonds to form chains running along the c axis.